Comprehending The Link Between CSR in SMEs in a Global Marketplace - Vargas Zeledon, Aaron Antonio (AMAR (Andalas Management Review), 2023)
Despite the rising interest, and existing huge literature on corporate social responsibility (CSR), up to now there is a scarce of research focused on small and medium-sized enterprises (SMEs) featured as discretionary about philanthropic actions mainly in small emerging markets, where is not an ecumenical assumed concept. This study address this issue by drawing upon the existing literature of CSR undertaking their actions to varying degrees in countless spaces particularly with special attention to the critical issue that cause SMEs either behind their setting to entrance global marketplace pertinent for firms’ strategic decisions in a world where CSR is often a viable tool, as well as seen as something more far-attainment, attractive at a much broader level with business operations and relations with markets that are more complex and turbulent time. In addition, CSR in some instances implicate institutional works pointed at tackling some gaps concerning the environment where SMEs operate. Derived from this, the current study present a set of propositions specifying the importance of useful insight issues consumers’ responses, norms and diffusion, competitiveness and social advantages, and forces preventing SMEs embarking in CSR on the business practices outlining a theoretical explanation. There are unavailable confronts for SMEs undertaking CSR, nonetheless by their very nature they have countless features that can aid the adoption of CSR, especially in small emerging markets.